Nanoporous Zn-doped Co3O4 sheets with single-unit-cell-wide lateral surfaces for efficient oxygen evolution and water splitting. (February 2018) - Liu, Xijun; Xi, Wei; Li, Chao; Li, Xibo; Shi, Jing; Shen, Yongli; He, Jia; Zhang, Lihan; Xie, Lin; Sun, Xiaoming; Wang, Peng; Luo, Jun; et al.
Abstract: Nanoporous Zn-doped Co3 O4 sheets with abundant lateral surfaces are developed. The lateral surfaces have single-unit-cell width (0.84 ± 0.03 nm) and contain more oxygen vacancies than conventional base/top surfaces, causing ultrahigh activity and durability for oxygen evolution and overall water splitting. Thus, the sheets are promising for practical and green hydrogen production. Graphical abstract: A Zn-doped Co3 O4 electrocatalyst consisting of nanoporous sheets was reported. The sheets contained abundant lateral surfaces with single-unit-cell width (0.84 ± 0.03 nm), which exposed more oxygen vacancies than conventional base and top surfaces, causing unparalleled performances when the sheets catalyzed oxygen evolution reaction (OER). They also efficiently catalyzed hydrogen evolution reaction (HER), enabling them to work as bifunctional electrodes for overall water splitting (OWS). Their performances for OWS were also unparalleled. Highlights: Nanoporous Zn-doped Co3 O4 sheets with abundant lateral surfaces are synthesized. The lateral surfaces exposed more oxygen vacancies than base and top surfaces. The sheets exhibit unparalleled performances for catalyzing OER in alkaline media. The sheets exhibit unparalleled performances for catalyzing OWS in alkaline media.